bell hooks and Kevin Powell: Black masculinity, threat or threatened - The New School (2015)
Join bell hooks and Kevin Powell in a discussion about black masculinity in popular culture today presented by Eugene Lang College of Liberal Arts (https://www.newschool.edu/lang) at The New School (https://www.newschool.edu/). Kevin Powell is an activist, public speaker and author of 12 books, including his new title The Education of Kevin Powell: A Boy’s Journey into Manhood. bell hooks is an author, activist, feminist and scholar-in-residence at The New School. This fall is her fifth and final week-long visit in a three-year residency.
Directors: _:n22023
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; fem3300; masculinité noire; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; états-unis